Developing countries in the world trading system : the Uruguay round and beyond - Athukorala, Prema-Chandra, ed (Cheltenham : Edward Elgar, 2002)
Economics
2003-04-16
Keywords: Developing countires; Developing countries-Economic conditions; Produce trade-Government policy; International trade-Social aspects; International trade-Environmental aspects; Clothing trade-Government policy; Uruguay; Brazil; Germany; Indonesia